2020
DOI: 10.3390/coatings10010051
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Chitosan/Sodium Phytate/Nano-Fe3O4 Magnetic Coatings on Wood Surfaces via Layer-by-Layer Self-Assembly

Abstract: Magnetic wood would have potential uses in electromagnetic shielding and electromagnetic wave absorption. In this paper, magnetic coatings on a wood surface were synthesized using a layer-by-layer self-assembly method. As the cationic polyelectrolyte carrier, natural macromolecular chitosan was pre-immobilized on a wood surface first, followed by the alternate adsorption of anionic polyelectrolyte sodium phytate and positively-charged Fe3O4 nanoparticles. The concentration of pH-controlled chitosan solution, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Due to decreasing fossil fuel resources and rapidly increasing environmental awareness, the utilization of renewable resources has become a focus of materials science research [1][2][3][4]. As a consequence, many novel bio-based materials have been developed and are expected to be utilized in many fields [5][6][7][8][9][10]. Wood-based materials (such as particleboard [11], plywood [12], oriented strand board [13], and fiberboard [14]) are common in everyday living environments, and are typically fabricated using formaldehyde-based resins to obtain excellent bonding performance [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to decreasing fossil fuel resources and rapidly increasing environmental awareness, the utilization of renewable resources has become a focus of materials science research [1][2][3][4]. As a consequence, many novel bio-based materials have been developed and are expected to be utilized in many fields [5][6][7][8][9][10]. Wood-based materials (such as particleboard [11], plywood [12], oriented strand board [13], and fiberboard [14]) are common in everyday living environments, and are typically fabricated using formaldehyde-based resins to obtain excellent bonding performance [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The developed coating was highly durable, keeping a contact angle higher than 150 • after UV exposition and degradation by HCl, NaOH, n-hexane, acetone, ethanol, DMF and boiling water. A magnetic wood coating based on chitosan, sodium phytate and nano-Fe 3 O 4 was prepared by Tang and Fu through layer-by-layer deposition [144]. They found that paramagnetic wood with narrow and long magnetic hysteresis loops could be created with this method, the magnetic properties of the treated wood being directly related to the number of layers in the coating.…”
Section: Organic-inorganic Composite Coatingsmentioning
confidence: 99%
“…These treatments, mostly belonging to the organic coatings' trends, included bio-based monomers for film-forming coatings [41][42][43][44]47], modified vegetal oils [39,40,45,46,51,55,56], biological polymers (chitosans, lignin, etc.) [57,58,92], and more [52,53,76,90,[143][144][145]. Many advantages come along with these materials, from the cradle to the grave.…”
Section: Ecological Aspectsmentioning
confidence: 99%
“…These LbL-assembled films on fibers result in new properties that are difficult to achieve with pulp fiber substrates [18][19][20][21]. Impregnated LbL self-assembly films have the advantage of simple equipment requirements and operational needs; however, disadvantages include the requirements of repeated impregnation, rinsing, and drying [22,23]. Moreover, the film formation is time-consuming; thus, impregnated LbL self-assembly film is a complicated procedure that has become one of the most significant bottlenecks in the development of this technology [24].…”
Section: Introductionmentioning
confidence: 99%